Outcomes of patent foramen ovale greater than 3 mm at birth in extremely low birthweight infants - Sheema Gaffar; Bijan Siassi; Rowena Cayabyab; Mahmood Ebrahimi; Lorayne Barton; Merujan Uzunyan; Rangasamy Ramanathan (BMC, 2023)
Abstract Background Foramen ovale (FO) is an obligate fetal shunt that typically resolves after birth, although patency throughout life is not uncommon. The natural history of patent FO (PFO) is known in term infants, but less is known about its course in extremely preterm infants. We describe the echocardiographic changes in FO size from birth to discharge in extremely low birth weight (ELBW) infants in this retrospective study. Methods Cohort was divided based on size of FO at birth. Size of FO at discharge was measured and evaluated relative to postnatal weight gain. Demographics and clinical outcomes were compared between the two groups. Results Of the 54 ELBW infants, 50 were born with FO less than 3 mm in diameter (small), and 4 were born with FO greater than 3 mm (large). Of small defects, the majority (44/50, 88%) did not increase in size with weight gain, and minority (6/50, 12%) increased in size, and three of these 6 patients, FO grew to be slightly larger than 3 mm. In contrast, all large defects (4 of 4, 100%) nearly doubled in size with postnatal growth. These 4 ELBW infants with enlargement of FO had a flap valve evident on echocardiogram obtained prior to discharge, and subsequently closed on outpatient follow-up echocardiograms, although time to resolution was variable (6 months - 3 years). One infant had presumptive resolution because of the presence of flap valve. Conclusion No maternal or neonatal demographic characteristics were predictive of FO enlargement, although, demonstrable flap valve on discharge echocardiogram correlated with resolution of FO on outpatient follow-up echocardiogram. Therefore, based on our data, we recommend that ELBW infants born with large FO should have echocardiographic re-evaluation of the atrial septal opening prior to discharge, to specify the presence of a flap valve or lack thereof, which is an important detail that can help a neonatologist determine the need for outpatient cardiac follow-up.